STREINGHT IN SWIMMING - Dejan Madić; Tomislav Okičić; Dimitrije Rašović; Slavica Okičić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Power is one of the basic factors that ensure the achievement of top sports achievements in swimming. This paper deals with methods and means for the development of specific strength in swimmers. Given the problems, this paper gives a certain contribution to the confirmation and correction of theoretical and empirical positions, primarily in the objective seeing, development and planning of training process.